Chemical Control of Root-Knot Nematodes in Established Vineyards - Loubser, J. T.; Deklerk, C. A. (South African Journal of Enology and Viticulture, 2017)
Chemical control of root-knot nematodes (Meloidogyne spp.) in established vineyards was investigated. A liquid soil fumigant (1,3-dichloropropene) and four systemic (nonfumigant) nematicides in granular form, viz. aldicarb, carbofuran, oxamyl and fenamiphos were applied as soil treatments during bud burst and after harvest. Significant average yield and cane mass increases were recorded during the three years following split treatment at bud burst with aldicarb and oxamyl and when aldicard was applied as a single treatment after harvest.